Early Greek Poets' Lives The Shaping of the Tradition - Kivilo, Maarit (Brill, 2010)
This book examines the formation and development of the biographical traditions about early Greek poets, focusing on the traditions of Hesiod, Stesichorus, Archilochus, Hipponax, Terpander and Sappho. The study provides a detailed overview of the traditions and chronographical material about these poets and seeks to clarify who were the creators of the particular traditions; what were the sources; when the traditions were formed; and to what extent they are shaped by formulaic themes and story-patterns. It challenges several mainstream assumptions on the subject, for example, that the traditions were formed mainly in the Post-Classical period; that the only significant source for the legends is the works of the particular poet; and that the poets were perceived as "new heroes."